Weapons of Mass Destruction and International Law - Abdullah, Mohammed Mahmood; Futaih, Raad Fejer; khalaf, Laith Rafea; Al-Obaidi, Bushra Salman Husain (Journal of Ecohumanism, 2024)
Background: Weapons of Mass Destruction (WMDs), biological and chemical weapons – have long presented serious dangers to global security. Recognizing the catastrophic potential of these weapons, the international community has worked to build legal frameworks to prevent their spread and deployment. Objective: With an emphasis on compliance methods and enforcement techniques, this article tries to assess international law’s effectiveness on WMDs critically. Methods: The Nuclear Non-Proliferation Treaty (NPT), the Biological Weapons Convention (BWC), and the Chemical Weapons Convention (CWC) were all thoroughly reviewed. In addition, case studies were examined to identify instances of noncompliance and the international reaction that followed. Results: International accords have successfully fostered transparency and disarmament, but problems remain. Noncompliance, often caused by differing interpretations of treaty duties or plain avoidance, continues to be a concern. Enforcement actions ranging from diplomatic discussions to sanctions and even military incursions have been used inconsistently, highlighting weaknesses in the international legal system. Conclusion: While the international legal system is essential for establishing norms and standards, it requires more consistent enforcement mechanisms and collaborative international efforts to be strengthened. Addressing the shortcomings of the existing framework is critical to ensuring a more secure future free of WMD threats.